Parental Involvement In Play Therapy - Ohlson, E. LaMonte (Canadian Journal of Counselling and Psychotherapy, 2012)
Psychologists and counsellors who work with children will readily agree that play is the essence and fortitude of a child's language, his most natural medium of self-expression. As it is important for the child to be able to "play out" his problems, one very necessary component all too often missing from the counsellor-child dyad is the parent. Therefore, not only does play therapy act as a medium of expression for children, but the therapist can and should utilize it as an effective technique whereby parents can better understand their children. When the counsellor decides that the therapy dyad is to include the parents, a well developed methodological approach on the part of the therapist is required. The purpose of this article is to outline a methodological approach as well as to emphasize the necessity of including the parent in the play therapy situation.